Application of Remote Sensing and GIS for Monitoring and Evaluation of the Reforestation Activities in Kupang district of East Nusa Tenggara - Irmadi Nahib; Jaya Wijaya (Forum Geografi, 1998)
To support reforestation activities, spatially forestry data are inexorably needed to support the activities. By using multi –temporally data, reforestation activities an be identified and detected. To accomplish the purpose, this research uses Landsat TM data aquired in 1990 and 1995. Remotely sensed data and Geographyc Information System (GIS) are methods that can be applied to gather, monitor as well as analyse data swiftly and accurately. This research uses remotely sensed data to collect land cover features in given area. Geographyc information System is used to capture and to analyse reforestation data. The expected is GIS based forest management strategy making.